Pelatihan Implementasi Metode Project Based Learning (PjBL) di SMAN 1 Banding Agung Kabupaten Ogan Komering Ulu Selatan - Sulistiawati, Sulistiawati; Lefudin, Lefudin; Lubis, Patricia H.M.; Lia, Linda; Sugiarti, Sugiarti; Hakim, Lukman (Universitas PGRI Palembang, 2024)
The implementation of Project Based Learning workshop in the framework of community service activieties was carried out on November 4, 2023 for teachers at SMAN 1 Banding Agung, South Ogan Komering Ulu Regency. The worshop aim is to apply the project based learning methode in subjects at the class. The training materials are: 1) Practical insight into the project based learning method, 2) How to analyze Basic Competensies (BC) that can be implemented in the project based learning model. 3) Practice selecting BC that can be aplly for project based learning methode. 4) Example of a lesson plan (RPP) that suitable for the project based learning method. 5) Examples of learning media that use the project based learning methode. 6) Exercise in preparing RPP using the project based learning method. 7) Evaluation. The results of the questionnaire that is given to training participants showed that the majority of training participants responded well to this training. According to them, the material presented is well organized, very relevant and as expected. The material provided makes it easier for them to provide understanding to colleagues to work together to improve/develop learning designs. The presenter was considered to really understand the material being presented and presented the material well and answered the participants' questions well.